Enhancing The SME’s Employee Careers Development: The Role of Organizational Learning - Basuki Basuki; Rahmi Widyanti (At-Tadbir : jurnal ilmiah manajemen, 2022)
An organization can grow quickly if it has a good knowledge culture. Employees are organizational assets that need their career development. Career development can only be ensured if the organization has a learning culture. This study examines and analyzes Employee Career Development through Organizational Learning Culture, Career Planning, and Career Management. This research was conducted on MSME employees with 259 respondents who gave answers collected from 60 MSMEs in the city of Banjarmasin. Data analysis using Structural Equation Modeling (SEM) with AMOS software. The study results found that there was a direct positive relationship between variables with different degrees of intensity. Empirically the four hypotheses have been proven, as well as there is a positive indirect relationship between the variables, proving the fifth hypothesis.